2022
DOI: 10.1097/aco.0000000000001156
|View full text |Cite
|
Sign up to set email alerts
|

Novel anesthetics in pediatric practice: is it time?

Abstract: Purpose of reviewSteadily mounting evidence of anesthesia-induced developmental neurotoxicity has been a challenge in pediatric anesthesiology. Considering that presently used anesthetics have, in different animal models, been shown to cause lasting behavioral impairments when administered at the peak of brain development, the nagging question, 'Is it time for the development of a new anesthetic' must be pondered. Recent findingsThe emerging 'soft analogs' of intravenous anesthetics aim to overcome the shortco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
(114 reference statements)
1
5
0
Order By: Relevance
“…The results showed that remimazolam has a non-inferior sedative effect than propofol and might be a safer alternative ( Xin et al, 2022b ). In addition, due to the characteristics of rapid conversion to inactive metabolites, remimazolam may reduce cumulative neurotoxicity, which will benefit pediatric patients compared to other commonly used anesthetics ( Useinovic and Jevtovic-Todorovic, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that remimazolam has a non-inferior sedative effect than propofol and might be a safer alternative ( Xin et al, 2022b ). In addition, due to the characteristics of rapid conversion to inactive metabolites, remimazolam may reduce cumulative neurotoxicity, which will benefit pediatric patients compared to other commonly used anesthetics ( Useinovic and Jevtovic-Todorovic, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some anesthetics drugs have also been reevaluated in different formulations, such as xenon and alphaxalone. However, their effects on brain development have yet to be established [ 58 ]. Certainly, this is another important issue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Post synaptic GABA A receptor interaction is the most common mode of action for anaesthetic and sedating drugs used in clinical anaesthesia and intensive care practice; for example, propofol, barbiturates, benzodiazepines, and inhaled drugs like isoflurane and sevoflurane. Unfortunately, those commonly used anaesthetic compounds have been shown to be neurotoxic, at least in immature brains [ 13 15 ], and the neurotoxic effects have been attributed to their interaction with GABA A receptors. This seems to be at odds with the fact that neurosteroids, allopregnanolone and progesterone are neuroprotective compounds even though they are sedatives and anaesthetics that interact with GABA A receptors [ 10 ].…”
Section: Discussionmentioning
confidence: 99%